Implementasi Penanganan Anak Tidak Sekolah dan Hambatan Sosial Ekonomi Kultural di Kawasan Pesisir Kelurahan Bulu - Tri Susilowati; Mamik Indaryani; Joko Utomo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the implementation of handling Out-of-School Children (ATS) through the Yuk Sekolah Maneh (YSM) Movement and identify the social, economic, and cultural barriers affecting it in the coastal area of Bulu Village, Jepara. The background of this research is the increasing number of ATS from 20 people (2023) to 31 people (2025). The research uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, and documentation. Data analysis used the interactive model of Miles and Huberman and Fishbone diagrams. The results show that the implementation of the YSM program is not optimal due to complex and interrelated barriers. Economic barriers in the form of structural poverty force children to work. Social barriers are reflected in weak parental supervision and peer influence. Cultural barriers are seen in the pragmatic views of coastal communities who consider work more important than school. From the government side, budget limitations and weak inter-agency coordination are the main obstacles. This study recommends improvement policy strategies including strengthening integrated data collection, differentiation of educational services, family economic empowerment, and strengthening multi-stakeholder coordination.